Faktor – Faktor Yang Memengaruhi Konsumsi Rumah Tangga Di 34 Provinsi Indonesia - Ricky Zulkarnain; Asih Murwiati (Departement of Mathematics Education, 2023)
Consumption describes the activities that people engage in at any given time. Consumption symbolizes one of the indicators to calculate the economy of a region. This study was conducted to see the points between the relationship between GRDP per capita, inflation, and the head of the beneficiary family on household consumption in 34 provinces of Indonesia in 2021. This analysis uses Ordinary Least Square analysis using cross section data with the Stata 15 analysis tool. This test reveals that there are two variables that have a positive and significant relationship with household consumption, namely the head of the beneficiary family and gross regional domestic product per capita. Then the inflation variable has a negative but insignificant relationship with household consumption.